Odor types determined by the major histocompatibility complex in germfree mice. - Yamazaki, K (1990)
The major histocompatibility complex (MHC) is the prime but not exclusive determinant of genetically specific constitutive body odors, termed odor types, represented strongly in urine of the mouse. Perception of MHC-determined odor types influences reproductive behavior in the contexts of mate choice and maintenance of early pregnancy, tending to favor the propagation of one MHC type over another. How MHC genotype determines MHC odor type is unknown. One possible explanation is that differential odorants are generated by populations of commensal microorganisms whose composition is somehow geared to MHC diversity. This hypothesis was tested in the Y-maze system in which mice are trained to distinguish the urinary odors of MHC-congenic mice. First, it was shown that mice could readily be trained to distinguish the urines of germfree MHC-congenic mice. Second, it was shown that mice trained to distinguish the urines of conventionally maintained MHC-congenic mice could as readily distinguish the urines of germfree MHC-congenic mice. These results imply that MHC-determined odor types do not depend on odorants generated by microorganisms.